Using mind mapping techniques to develop Ly Thuong Kiet high school 11th grade students’ reading text summary skills - Nguyễn, Thị Thúy Vân (University of Languages and International Studies, 2017)
This study was done aiming at finding out the more useful teaching methods for improving students’ reading text summary skills, testing the effectiveness of using mind-mapping techniques to develop 11th grade students’ reading text summary skills.